An Analyzing of Deixis on Donald Trump’s Speech : “State of The Union Address” - Hidayah, S.S, M.A, Arini; Saraswati, Ire (JURNAL PENDIDIKAN, 2024)
This research is a descriptive qualitative research. The data in this study is speech of Donald Trump’s Speech analyzed.Data analysis was performed by categorizing data by type according to theory from Yule of type and function deixis.The goals of this research are to find out five kinds and functions of deixis used in Donald Trump’s Speech and the function of deixis. The techniques of the collecting data in this research are watching, writing and segmenting. After collecting the data the researcher analyzes the data that include five kinds of deixis. From the analysis the researcher found 567 deixis. Those are 404 person deixis, 90 time deixis, 35 place deixis, 18 social deixis and 20 discourse deixis. It found in Donald Trump’s Speech which contain five kinds of deixis: person deixis, time deixis, place deixis, social deixis and discourse deixis. Then, the researcher explains the data by descriptive explanation. The most dominant of types deixis appears in each speech of the person deixis (71,2%). It is becaused the utterance mostly refer to the person or the audience. The submissive of the data are the social deixis (3,1%) because the speaker used the person name more generally than social deixis as the surname. This speech is explaining about purposes and changes of United States. This speech more explain about smuggling, economy, illegal trade, terrorist and cancer in America.